Agriculture en Roumanie: définir l’activité pour un ciblage de la politique des structures - Marie-Luce Ghib; Marielle Berriet-Solliec (Romanian Journal of European Affairs, 2010)
Like the former member States of the EU in 1962 at the beginning of the CAP, today Romania focuses mainly on the restructuring and the modernisation of its agriculture. In a general context in which OECD advocates the targeting of farm holdings to achieve a better efficiency of agricultural policies, we analyse in this paper the difficulties for a definition for targeting the units in the Romanian context. The article draws parallels between different types of production structures in Romania, as they can be defined with the current statistical apparatus, and the objectives aimed by the principal measures of the rural development policy. It concludes with an analysis of the adequacy of the system chosen in Romania to accompany the modernisation, the restructuring and the reorientation of farm holdings.